THE SOLUTION OF PROBLEMS OF MECHANICS OF THE DEFORMABLE SOLID BODY WITH USE OF FICTITIOUS SETTLEMENT SCHEMES - G. E. Agakhanov (Вестник Дагестанского государственного технического университета: Технические науки)
Using the fictitious settlement schemes based on equivalence of influences in mechanics of a deformable solid body the intense deformed states are received for the beam on two support which is under the influence of mass forces; the rotating thin round disk; the dam of triangular cross section which is under the influence of volume filtrational forces.